2017
DOI: 10.1002/mmce.21201
|View full text |Cite
|
Sign up to set email alerts
|

Minimum information for dielectric measurements of biological tissues (MINDER): A framework for repeatable and reusable data

Abstract: The dielectric properties of biological tissues characterise the interaction of human tissues with electromagnetic (EM) fields. Accurate knowledge of the dielectric properties of tissues are vital in EM‐based therapeutic and diagnostic techniques, and for assessing the safety of wireless devices. Despite the importance of these properties, the field has suffered from inconsistencies in reported data. The dielectric measurement process for tissues is known to be affected by both measurement confounders and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 60 publications
0
28
1
Order By: Relevance
“…As one of the significant factors for change of dielectric properties is the dehydration of tissue, the samples were sealed in small sealed plastic containers to minimize this effect. While in vivo dielectric property characterization is ultimately desired, several studies have noted the challenges of measuring dielectric properties of tissue in vivo with invasive probes . Furthermore, in this study, only normal lung tissue was considered.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the significant factors for change of dielectric properties is the dehydration of tissue, the samples were sealed in small sealed plastic containers to minimize this effect. While in vivo dielectric property characterization is ultimately desired, several studies have noted the challenges of measuring dielectric properties of tissue in vivo with invasive probes . Furthermore, in this study, only normal lung tissue was considered.…”
Section: Discussionmentioning
confidence: 99%
“…The developed probe was also less affected by measurement technique variability. Further, Porter et al [49] observed that histology depth (defined as the depth to which the probe can detect changes in the tissue sample within the measurement uncertainty) varies with frequency, and hence, it should have been included as a con-founder in historic data sets (like Lazebnik et al) where the histology depth was taken as a constant value. In 2018, it was further noted that the probe sensing radius could be smaller than the probe radius and depended on the histology of the tissue sample [48].…”
Section: Dielectric Property Contrast: the Backbone Of Mwimentioning
confidence: 99%
“…In 2018, it was further noted that the probe sensing radius could be smaller than the probe radius and depended on the histology of the tissue sample [48]. MINDER (Minimum Information for Dielectric Measurements of Biological Tissues) model was developed by the team which allows to reproduce measurements, provides ease of interpreting and reusing data, and comparison of data across studies [49].…”
Section: Dielectric Property Contrast: the Backbone Of Mwimentioning
confidence: 99%
“…We took the Minimum Information for Dielectric Measurements of Biological Tissues (MINDER), proposed in Reference [ 36 ], as a guideline to collect experimental data and associated metadata. MINDER specifications indicate a systematic collection of metadata along with dielectric measurement data, in order to support a more informed sharing and re-use of dielectric data.…”
Section: Dielectric Properties Measurement Of Lymph Nodesmentioning
confidence: 99%